2017
DOI: 10.1080/02656736.2017.1402130
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of mobile insulator sheets for the optimisation of deep heating area for regional hyperthermia using a capacitively coupled heating method: phantom, simulation and clinical prospective studies

Abstract: Our novel heating method using mobile insulator sheets was thus found to improve the thermal dose parameters. Further investigations are expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The insertion of a bolus of the 5% salt solution, which has high electrical conductivity, in the IGC area could allow the RF current to concentrate to the IGC with reduction of RF current to the buttock fat and could improve the temperature increase in the deep target tumor just below the IGC. Our group previously reported that the heating technique of inserting insulator sheets between the RB and OB and moving them temporally could improve the temperature increase for the prostate cancer of the deep pelvic tumor [ 30 ]. However, the weakness of the heating method using mobile insulating sheets is that it requires rotations of the insulating sheets temporally, which is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of a bolus of the 5% salt solution, which has high electrical conductivity, in the IGC area could allow the RF current to concentrate to the IGC with reduction of RF current to the buttock fat and could improve the temperature increase in the deep target tumor just below the IGC. Our group previously reported that the heating technique of inserting insulator sheets between the RB and OB and moving them temporally could improve the temperature increase for the prostate cancer of the deep pelvic tumor [ 30 ]. However, the weakness of the heating method using mobile insulating sheets is that it requires rotations of the insulating sheets temporally, which is time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Electromagnetic and thermal simulations were performed using the multiphysics simulation platform Sim4Life (Zurich Med Tech, Zurich, Switzerland) 2325 . A three-dimensional mouse model, reconstructed from computed tomography images, was used for the simulations as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical applications of electromagnetic locoregional heating. Capacitive locoregional heating has been investigated for several tumor locations, such as lung [78][79][80][127][128][129], prostate [130,131], bladder [81,132,201], rectum [133,134] and liver [82,83], and treatments were generally deemed feasible. Degrees of clinical success are usually varying, but good clinical results can be achieved with capacitive hyperthermia, provided that the patient has only a thin superficial fat layer [29].…”
Section: Electromagnetic Locoregional Heatingmentioning
confidence: 99%